The Protective Roles of Dietary Selenium Yeast and Tea Polyphenols on Growth Performance and Ammonia Tolerance of Juvenile Wuchang Bream (Megalobrama amblycephala) - Guo, Honghui; Lin, Wang; Hou, Jie; Wang, Lingkai; Zhang, Dandan; Wu, Xueyang; Li, Li; Li, Dapeng (Frontiers in Physiology, 2018)
In order to investigate protective roles of dietary selenium yeast and tea polyphenols on growth of juvenile Wuchang bream (Megalobrama amblycephala) and its resistance under ammonia stress, juvenile Wuchang bream were randomly assigned into four groups: a control group fed basal diets and three treatment groups fed basal diets supplemented with 0.50 mg/kg selenium yeast, 50 mg/kg tea polyphenols and a combination of 0.50 mg/kg selenium yeast and 50 mg/kg tea polyphenols respectively. After 60 d of feeding, growth parameters of Wuchang bream were measured along with serum hormones and the transcription of growth axis-related genes. Then fish were exposed to ammonia stress of 22.5 mg/L total ammonia nitrogen. Hepatic oxidative damage parameters, antioxidant responses and ultrastructure were evaluated before ammonia exposure (0 h) and at 3, 6, 12, 24 and 48 h after ammonia exposure. Results show that before ammonia exposure, the growth parameters, serum GH and IGF-1 levels as well as the growth axis-related gene expression (gh, ghr2 and igf-1) for the selenium yeast and combination groups were higher than those determined for the fish on the control diet. In contrast, the administration of TP alone didn’t have significant effects on the growth parameters and growth-related hormones. After ammonia exposure, compared with the control, remarkable increases in the activity and mRNA expression of hepatic antioxidant enzymes (glutathione peroxidase and catalase superoxide dismutase) in three treatment groups were observed along with decreases of hepatic malondialdehyde and protein carbonylation levels, indicating that the single and combined supplementation of selenium yeast and tea polyphenols could enhance antioxidant capacity to alleviate oxidative stress and damage by ammonia. Consistent with this finding, alterations of the liver ultrastructure in three treatment groups were less severe and faster recovery than in the control group after ammonia exposure. In conclusion, a basal diet supplemented with the combination of 0.50 mg/kg selenium yeast and 50 mg/kg tea polyphenols could has very beneficial effects on the whole aspects of the growth and ammonia resistance in Wuchang bream juveniles. Keywords: ammonia stress; selenium yeast; tea polyphenols; gene expression; ultrapathology; Wuchang bream